2004
DOI: 10.1518/hfes.46.2.205.37340
|View full text |Cite
|
Sign up to set email alerts
|

Verification of the Change Blindness Phenomenon While Managing Critical Events on a Combat Information Display

Abstract: Change blindness occurs when humans are unable to detect significant changes in objects and scenes after their attention is momentarily diverted. Because change blindness is relevant in many applied settings, the current study investigated the phenomenon in the context of tasks performed by naval command and control system personnel. Operators of such systems are often heavily loaded with concurrent visual search, situation assessment, voice communications, and control-display manipulation tasks at large, phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 17 publications
3
31
0
Order By: Relevance
“…In fact, the participant reported that before taking part in the study, he was unaware of how often he was distracted until he started using our techniques. This finding complements research into change blindness that suggests that people are not fully aware of their inability to perceive visual changes [3,8]. Based on our study, we conjecture people may be unaware of the extent to which they get distracted by visual display changes in their environment.…”
Section: Approachsupporting
confidence: 73%
See 2 more Smart Citations
“…In fact, the participant reported that before taking part in the study, he was unaware of how often he was distracted until he started using our techniques. This finding complements research into change blindness that suggests that people are not fully aware of their inability to perceive visual changes [3,8]. Based on our study, we conjecture people may be unaware of the extent to which they get distracted by visual display changes in their environment.…”
Section: Approachsupporting
confidence: 73%
“…However, the effects of change blindness in multi-display environments have not been extensively studied in the literature. In one study, DiVita and colleagues [8] report that change blindness was a significant factor for operators managing critical events using multi-display command and control systems with unattended displays.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual limitations have also been reported to affect the ability of people to correctly detect the presence of changes introduced between one visual scene and the next, both in laboratory settings, and under more ecologically valid conditions (showing people surprisingly failing to perform this task accurately; a phenomenon known as "change blindness"; e.g., DiVita, Obermayer, Nugent, & Linville, 2004;French, 1953;Grimes, 1996;Hochberg, 1968;Rensink, 2002;Velichkovsky, Dornhoefer, Kopf, Helmert, & Joos, 2002).…”
Section: Central Limitations Of Unimodal Information Processingmentioning
confidence: 99%
“…Change detection has also been examined during the performance of tasks involved in important real-world work environments. For example, change blindness was demonstrated for operators of naval Combat Information Center (CIC) consoles as they performed their task of monitoring several visual displays simultaneously (Divita, Obermayer, & Nugent, 2004). Divita et al (2004) also noted that monitoring visual displays is common to real world professions in nuclear power plants, air traffic control centers, crisis response centers, and hospital emergency rooms.…”
mentioning
confidence: 99%